Six Month Follow-Up of Patient Reported Outcomes Following Third Generation Minimally Invasive Chevron Akin Osteotomies (MICA) in Hallux Valgus Surgery. Issue 4 (22nd October 2020) - Lewis, Thomas L.; Ray, Robbie; Gordon, David
Category: Bunion Introduction/Purpose: The aim of this study was to explore the short-term results of third generation (using screw fixation) Minimally Invasive Chevron and Akin osteotomies (MICA) for hallux valgus correction. There is a paucity of published data regarding the outcomes of this relatively new technique. We present the largest series in the literature, using three separate validated patient-reported outcome measures (EQ-5DL, VAS Pain and Manchester Oxford Foot Questionnaire (MOXFQ), for this time point. Methods: A single surgeon case series of patients with hallux valgus underwent primary third generation minimally invasive chevron and akin osteotomies for hallux valgus correction. Between August 2015 and July 2019, 478 MICAs were performed in 328 patients that were eligible for 6 month follow up. Baseline and 6 month post-operative patient reported outcomes were collected for 340 feet in 267 patients (247 females; 20 males). Paired t-tests were used to determine the statistical significance of the difference between pre- and post-operative scores. Results: The mean age was 54.9 (range 16.3-84.9, standard deviation (s.d.) 12.8). At 6 month follow up, the mean MOXFQ scores had improved for each domain: Pain; baseline 42.5 (range 0-100, s.d. 22.6), reduced to 16.3 (range 0-100, s.d. 18.4, p<0.001); Walking; baseline 35.5 (range 0-100, s.d. 24.8), reduced to 12.2 (range s.d. 19.1, p<0.001); Social interaction; baseline 45.4 (range 0- 100, s.d. 22.6), reduced to 10.9 (range 0-100.0, s.d. 16.9, p<0.001). Mean VAS Pain score improved from 30.5 (range 0.0-90.0, s.d. 22.1) to 10.5 (range 0.00-78.0, s.d. 14.8, p<0.001). Mean EQ-5D index score improved from 0.752 (range 0.066-1.000, s.d. 0.133) to 0.872 (range 0.122-1.000, s.d. 0.133, p<0.001). Mean EQ-5D VAS score remained static from 82.7 (range 0-100, s.d. 13.3) to 83.7 (range 0-100, s.d. 17.8, p=0.386). Conclusion: This is the largest prospective case series of short-term patient reported outcomes using a validated assessment method for hallux valgus, following third generation MICA to date. These data show that this technique is effective at improving foot and ankle specific patient reported outcomes at 6 months. This cohort is being followed over the longer term.